(untitled) (Vallis Aurea, 2015)
The struggle forrevenue, profitand financial added value, imageand customer added valuein the globaltourism industrytodayis directly manifested in the intense competitionbetween the massall inclusive tourism and theuniqueandindividuallyorientedboutiquetourist product. The leadershipin profittodayis a result of theflexibility, creativity and innovation of thestrategy used, and in the opposition"all inclusivetourism -boutique tourist accommodation" the emphasis making adifferenceis not limited to prices,services, quality and number of tourists only. The essentialdifference consists inthe clash ofstrategies with different philosophyandtarget audiences-diversification,differentiationand costleadershipapplied by theall-inclusive-tourismstrategyas opposed to the strategy offocusing which istypical ofboutique hotelsanddestinations.Despite the differentstrategic approaches, the goal is one and the same -leadershipin terms ofgeneratedprofits.